Cyclophilin A: promising target in cancer therapy - Shujuan Jin; Mengjiao Zhang; Xiaoting Qiao (Cancer Biology & Therapy)
Cyclophilin A (CypA), a member of the immunophilin family, stands out as the most prevalent among the cyclophilins found in humans. Beyond serving as the intracellular receptor for the immunosuppressive drug cyclosporine A (CsA), CypA exerts critical functions within the cell via its peptidyl-prolyl cis-trans isomerase (PPIase) activity, which is crucial for processes, such as protein folding, trafficking, assembly, modulation of immune responses, and cell signaling. Increasing evidence indicates that CypA is up-regulated in a variety of human cancers and it may be a novel potential therapeutic target for cancer treatment. Therefore, gaining a thorough understanding of CypA’s contribution to cancer could yield fresh perspectives and inform the development of innovative therapeutic approaches. This review delves into the multifaceted roles of CypA in cancer biology and explores the therapeutic potential of targeting CypA.